Assessing modifications in burned areas characteristics to monitor land-use changes and landscape fragmentation around the WAP Complex of protected areas (West Africa) (2005)
The conversion of natural biotopes into human managed environments has major ecological effects both in terms of loss of habitat and of alteration of landscapes’ spatial configuration (Forman, 1997). Monitoring land-cover changes in natural habitats is thus of primary importance for conservation. In sub-Saharan Africa fires are widespread and accompany the process of management and modification of the land (Grégoire, 1996. Clerici et al., 2004). Fires are used as a tool to clear vegetation, to induce re-sprouting for pasture, to facilitate crop fields’ preparation and for hunting purposes. The fragmentation of natural habitats due to land-cover change processes influences in turn the extension of fires and their distribution, creating discontinuities in the previous more homogeneous vegetation strata; there is therefore a feedback chain where fires accompany the landscape fragmentation process and changes in fragmentation modify the geometric characteristics and distribution of burned areas.